2014
DOI: 10.1517/14712598.2015.960837
|View full text |Cite
|
Sign up to set email alerts
|

Placental mesenchymal stem cells of fetal origin deposit epigenetic alterations during long-term culture under serum-free condition

Abstract: The fPMSCs cultured in serum-free medium have a tendency to deposit methylation modifications over in vitro expansion, therefore the detection of genetic and/or epigenetic alterations is necessary for fPMSCs before they are employed for clinical uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…In light of this, bulk manufacturing protocols for hAMSC and hCMSC with the ability to maintain vigorous growth and stable karyotypes will need to be developed if widespread clinical translation of their pro‐regenerative and pro‐reparative potential is to be realized. Given recent reports on the importance of MSC priming and impact of biomatrix stiffness on stem function , these factors should also be given due consideration in protocol development for bulk cutures.…”
Section: Yields and Growth Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of this, bulk manufacturing protocols for hAMSC and hCMSC with the ability to maintain vigorous growth and stable karyotypes will need to be developed if widespread clinical translation of their pro‐regenerative and pro‐reparative potential is to be realized. Given recent reports on the importance of MSC priming and impact of biomatrix stiffness on stem function , these factors should also be given due consideration in protocol development for bulk cutures.…”
Section: Yields and Growth Characteristicsmentioning
confidence: 99%
“…Unlike MSC from bone marrow and adipose tissues, expansion of hAMSC and hCMSC in vitro is contentious where some report poor expansion beyond five passages [43], and others report a stable karyotype after 20 passages over a period of 120 days [53]. Serial expansion of stem cells from gestational tissues, albeit with placental MSC, has also been previously shown to be associated with epigenetic alterations when the cells were passaged under serum-free conditions [54]. This may be a cause for concern since the dominant epigenetic changes observed were demethylation of genes associated with ageing and tumorigenesis.…”
Section: Yields and Growth Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main prerequisite of stem cell-based therapies application is obtaining their adequate amount by expansion in vitro. The time of culture seem to be critical because several studies described changes of biological properties of stem cells during prolonged cultivation (Nava et al, 2015;Zhu et al, 2015). The present study was therefore aimed at analysis of selected biological and morphological properties of ATSCs during prolonged culture in vitro up to 10th passage.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have indicated that MSCs derived from placenta of fetal origin possess greater therapeutic potential compared with MSCs isolated from other tissues and organs [1,2]. Several studies support the ability of these MSCs either to repair or regenerate damaged myocardium [35], although their long-term durability in tissue is controversial [6,7].…”
Section: Introductionmentioning
confidence: 99%